A meta-analysis of influenza vaccination following correspondence: Considerations for COVID-19. Issue 52 (20th December 2021) - Murphy, Robert P.; Taaffe, Carol; Ahern, Elayne; McMahon, Grace; Muldoon, Orla
Highlights: Written messages to members of the community increases influenza vaccine uptake. This is effective across correspondence type, age group, time, and location. Vaccine correspondence commonly recommends it, says it avoids illness and where to get it. Uptake may be higher if correspondence is from a care provider rather than an insurer. Abstract: Background: High vaccination rates are needed to protect against influenza and to end the COVID-19 pandemic. Health authorities need to know if supplementing mass communications with direct correspondence to the community would increase uptake. Objectives: The primary objective is to determine if sending a single written message directly to individuals increases influenza vaccine uptake, and a secondary objective is to identify any identified content shown to increase influenza vaccine uptake. Methods: MEDLINE, Embase, Cochrane CENTRAL, PsycINFO, and PubMed were searched for RCTs testing a single correspondence for members of the community in OECD countries to obtain influenza vaccination. A meta -analysis with inverse-variance, random-effects modelling was used to estimate a mean, weighted risk ratio effect size measure of vaccine uptake. Studies were quality assessed and analysis was undertaken to account for potential publication bias. Results: Twenty-eight randomized controlled trials were included, covering 45 interventions. Of the 45 interventions, 37 (82.2%) report an increase in influenza vaccination rates. A formal meta -analysis shows that sending a single written message increased influenza vaccine uptake by 16%, relative to the no contact comparator group (RR = 1.16, 95% CI [1.13–1.20], Z = 9.25, p  < .001). Analysis shows that the intervention is effective across correspondence type, age group, time, and location, and after allowing for risk of publication bias. Limitations: The generalizability of results across the OECD may be questioned. Conclusions and implications: The implication for public health authorities organizing vaccination programs for influenza, and arguably also for COVID-19, is that sending written vaccination correspondence to members of the community is likely to increase uptake. This study is pre-registered on osf.io; details can be found at https://osf.io/98mr7 .